Chromosome Numbers of some Nepalese Flora - Vaidya, Buddha Laxmi; Manandhar, Laxmi (Journal of Natural History Museum, 2015)
Previous and present chromosome counts of 10 Nepalese taxa within 7 families viz. Amaryllidaceae, Asteraceae, Caricaceae, Leguminosae, Nyctaginaceae, Passifl oraceae and Scrophulariaceae are reported here. Diploid or haploid chromosome numbers of the taxa collected from the local gardens of Kathmandu are n=15 in Agapanthus africanus (L.) Hoffmanns (Amaryllidaceae); 2n=48+3B in Allium tuberosum Rottler ex Spreng. (Amaryllidaceae); 2n=18 in Artemisia indica Willd. (Asteraceae); 2n=27 in Carica papaya L. (Caricaceae); 2n=16 in Cicer arietinum L., 2n=14, 21 in Pisum sativum L., 2n=12 in Vicia faba L. (Leguminosae); 2n=28 in Bougainvillea glabra Choisy (Nyctaginaceae); 2n=18 in Passiflora edulis Sims. (Passifloraceae) and 2n= 34 in Bacopa monnieri (L.) Pennel (Scrophulariaceae) in the present research. Of these, the chromosome count of Bougainvillea glabra in this research is perhaps the new report. The reports of chromosome number in Artemisia indica, Carica papaya and Bacopa monnieri in the present investigation are confirmed to be different from the previously reported numbers for these taxa. The chromosome number of Agapanthus africanus, Allium tuberosum, Cicer arietinum, Passiflora edulis, Pisum sativum, Vicia faba in the present research tally with the previous reports. The present counts in Bacopa monnieri, Carica papaya and Passiflora edulis are new records for Nepal.J. Nat. Hist. Mus. Vol. 28, 2014: 18-33